2007
DOI: 10.1523/jneurosci.2461-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiling of Huntington's Disease Models Suggests That Brain-Derived Neurotrophic Factor Depletion Plays a Major Role in Striatal Degeneration

Abstract: Many pathways have been proposed as contributing to Huntington's disease (HD) pathogenesis, but generally the in vivo effects of their perturbation have not been compared with reference data from human patients. Here we examine how accurately mechanistically motivated and genetic HD models recapitulate the striatal gene expression phenotype of human HD. The representative genetic model was the R6/2 transgenic mouse, which expresses a fragment of the huntingtin protein containing a long CAG repeat. Pathogenic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
161
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(167 citation statements)
references
References 47 publications
6
161
0
Order By: Relevance
“…It is believed that transplantation of ADMSCs affected both central and peripheral cholinergic and motor neurons, because an increase in ACh release is related to behavioral activation (Mizuno et al, 1991), and muscarinic agonists improve locomotor behavior in aged animals (Glenn et al, 2004). Moreover, restoration of activity was contributed not only by BDNF involved in dopaminergic function and motor coordination (Strand et al, 2007;Boger et al, 2011) but also by NGF upregulating cholinergic activity (Pongrac and Rylett, 1998;Oosawa et al, 1999;Auld et al, 2001), because neurotrophins, including BDNF and NGF, play roles in skeletal muscle adaptation (Sakuma and Yamaguchi, 2011). The degree of recovery of physical activity was similar among the groups, regardless of injection route and dosage of ADMSCs, suggesting a major role for peripheral effects on neuromuscular transmission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that transplantation of ADMSCs affected both central and peripheral cholinergic and motor neurons, because an increase in ACh release is related to behavioral activation (Mizuno et al, 1991), and muscarinic agonists improve locomotor behavior in aged animals (Glenn et al, 2004). Moreover, restoration of activity was contributed not only by BDNF involved in dopaminergic function and motor coordination (Strand et al, 2007;Boger et al, 2011) but also by NGF upregulating cholinergic activity (Pongrac and Rylett, 1998;Oosawa et al, 1999;Auld et al, 2001), because neurotrophins, including BDNF and NGF, play roles in skeletal muscle adaptation (Sakuma and Yamaguchi, 2011). The degree of recovery of physical activity was similar among the groups, regardless of injection route and dosage of ADMSCs, suggesting a major role for peripheral effects on neuromuscular transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, BDNF is also involved in the development of motor coordination (Strand et al, 2007). Several studies have demonstrated that age-and AD-related dysfunctions of the cholinergic system related to physical activity as well as cognitive function are ameliorated by NGF and BDNF treatment (Williams et al, 1986;Casamenti et al, 1994;Kordower et al, 1994;Murray et al, 1994).…”
mentioning
confidence: 99%
“…Thus, BDNF impairment appears to be a key factor in the pathology of the HD. Indeed, comparative analysis of gene expression profiles of striatal tissues from BDNF knockout mice with those from a postmortem HD patient, and those from HD rodent models including 3-nitropropionic acid-lesioned or transgenic models showed that the BDNF knockout model profile is more comparable to human HD than the other murine HD profiles [114].…”
Section: Bdnf Induces a Neuronal Addition To The Adult Striatummentioning
confidence: 99%
“…To develop a quantitative, cell-based preclinical assay system for HD, we have focused on a well-characterized early feature of disease pathology in both these animal models and HD patients, transcriptional dysregulation in the medium spiny neurons (MSNs) of the basal ganglion, a phenotype with substantial consistency among mouse models and between the models and patients (3)(4)(5)(6). One such dysregulated gene, dopamine receptor D2 (DRD2 or D2), shows high expression levels in MSNs of the indirect pathway (striatopalladial) of the basal ganglion, which are among the earliest to die in HD (reviewed in ref.…”
mentioning
confidence: 99%